KAPABILITAS INOVASI USAHA KECIL DAN MENENGAH DI INDONESIA - Irsan Tricahyadinata (AKUNTABEL, 2013)
The Importance of studying innovation in context of small firms lies the fact that: there is no specific size of a company that is more suited for innovation, and small companies have barriers and determinants of different innovations. Improve SMEs innovation to create competitiveness is not an easy thing to do. In Indonesian, the government's efforts merely provide help with various aspects of the capital program People's Business Credit (KUR), which largely devoted to productive activities such as SMEs. However, the existing problems are not only limited in terms of capital, some other problems such as lack of access to SMEs companies with banking institutions, business-oriented business management weaknesses, knowledge and information are lame so forth. On the external side, the cultural import cheaper reasons and also the high competition of goods and services from abroad who supported the means and funds to trigger depressed SMEs with limited capital. Finally not a lot of SMEs in Indonesia that can grow and develop strong as expected. Strategy is to be able the competition through innovation. Study more complex models and relevant in explaining the innovation and performance of SMEs in Indonesia that can conveniently be considered in practical policies related to efforts on improve the company's innovation and SMEs performance both in terms of companies and other stakeholders which means importance role of market orientation, leaderships, culture organization and partnership organization for innovation (process, product and market) and performance.Keywords: Performance; Capabilities Inovation: SMEs Indonesian